2013
DOI: 10.1152/ajpcell.00408.2012
|View full text |Cite
|
Sign up to set email alerts
|

Oatp58Dc contributes to blood-brain barrier function by excluding organic anions from the Drosophila brain

Abstract: The blood-brain barrier (BBB) physiologically isolates the brain from the blood and, thus, plays a vital role in brain homeostasis. Ion transporters play a critical role in this process by effectively regulating access of chemicals to the brain. Organic anion-transporting polypeptides (Oatps) transport a wide range of amphipathic substrates and are involved in efflux of chemicals across the vertebrate BBB. The anatomic complexity of the vascularized vertebrate BBB, however, creates challenges for experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…The Drosophila genome encodes eight Oatp transporters, two of which have enriched transcript number in the Drosophila brain ( Oatp58Dc and Oatp74D ; http://flyatlas.org/ ). Seabrooke and O'Donnell ( 2013 ) have recently shown that Oatp58Dc is expressed in the PG, SPG and post-mitotic neurons, and is required specifically in PG cells for maintaining chemical protection of the brain from fluorescein. In the absence of Oatp58Dc, levels of hemolymph-injected fluorescein are higher in the brains of Oatp58Dc Drosophila brains.…”
Section: Molecular Overview Of the Invertebrate Bbbmentioning
confidence: 99%
See 3 more Smart Citations
“…The Drosophila genome encodes eight Oatp transporters, two of which have enriched transcript number in the Drosophila brain ( Oatp58Dc and Oatp74D ; http://flyatlas.org/ ). Seabrooke and O'Donnell ( 2013 ) have recently shown that Oatp58Dc is expressed in the PG, SPG and post-mitotic neurons, and is required specifically in PG cells for maintaining chemical protection of the brain from fluorescein. In the absence of Oatp58Dc, levels of hemolymph-injected fluorescein are higher in the brains of Oatp58Dc Drosophila brains.…”
Section: Molecular Overview Of the Invertebrate Bbbmentioning
confidence: 99%
“…Eight potential SLC21 (Oatp) transporters have been identified in Drosophila (Seabrooke and O'Donnell, 2013 ). Of these eight, four are expressed in the Drosophila head or brain ( Oatp30B, Oatp33Ea, Oatp58Dc , and Oatp74D ; http://flyatlas.org/ ; Torrie et al, 2004 ; Seabrooke and O'Donnell, 2013 ).…”
Section: Molecular Overview Of the Invertebrate Bbbmentioning
confidence: 99%
See 2 more Smart Citations
“…Given their conserved biological function, members of the Mdr and Oatp families are prime candidates for adaptive evolution (Dobler et al, 2015; Petschenka and Agrawal, 2016). Together with work showing the protective effects of Mdrs and Oatps against plant-derived toxins and pesticides (Dermauw and Van Leeuwen, 2014; Seabrooke and O’Donnell, 2013; Torrie et al, 2004), these findings have led to the hypothesis that the broad-substrate Mdrs and Oatps might have a general role in excluding plant toxins at the gut membrane and BBB, and in excreting toxins at the Malpighian tubules (Dobler et al, 2015). The high level of amino acid sequence conservation across animals suggests that these transporters could provide some resistance against cardenolides in most insects.…”
Section: Introductionmentioning
confidence: 97%